Uncomfortable relations: writers, work and money in the 1920s. The case of Nicolás Olivari (Anclajes, 2015)
In the 1920s, Olivari´s work as well as his trajectory allows to study the always intricate relations between literature and money. At a time marked by the modernization process and the enlargement of the cultural field, there was a change in the modes of imagining and building the social identity of the writer, who also had to ensure his/her source of revenue.  In this context, the “worker writer” and/or the “journalist writer” figures emerged as some complex and unstable answers the culture producers rehearsed.
Keywords: 1920s; professionalization; cultural market; journalism; Nicolás Olivari